2011
DOI: 10.1016/j.neulet.2011.01.045
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic amelioration of severe hypoglycemia-induced neuronal damage

Abstract: Hypoglycemia is a common complication for insulin treated people with diabetes. Severe hypoglycemia, which occurs in the setting of excess or ill-timed insulin administration, has been shown to cause brain damage. Previous pre-clinical studies have shown that memantine (an Nmethyl-D-aspartate receptor antagonist) and erythropoietin can be neuroprotective in other models of brain injury. We hypothesized that these agents might also be neuroprotective in reponse to severe hypoglycemia-induced brain damage. To te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…Our findings, however, support the results of these studies [17], [19] and add to the results from cellular and animal studies showing that EPO protects and enhances the function of cerebral cells lacking substrate [13][15], [31]. Moreover, a recent study by Silverstein and coworkers has shown that erythropoietin ameliorates hypoglycemic brain damage in rats [16].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings, however, support the results of these studies [17], [19] and add to the results from cellular and animal studies showing that EPO protects and enhances the function of cerebral cells lacking substrate [13][15], [31]. Moreover, a recent study by Silverstein and coworkers has shown that erythropoietin ameliorates hypoglycemic brain damage in rats [16].…”
Section: Discussionsupporting
confidence: 90%
“…At supraphysiological circulating concentrations EPO penetrates the intact human blood brain barrier [12]. In vitro studies suggest that EPO preserves cellular function during hypoglycemia [13][16]. In healthy adults high dose intravenous EPO treatment modulates neuronal processing and may improve cognitive function 7 days after administration of EPO [17], [18].…”
Section: Introductionmentioning
confidence: 99%
“…Four to ten days postsurgery, overnight fasted, precannulated, awake, unrestrained rats were subjected to hyperinsulinemic (0.2 units ⋅ kg −1 ⋅ min −1 ) severe hypoglycemic (10–15mg/dL) clamps as previously described (2830). Hypoglycemia was maintained for a predetermined duration (60 min for studies 1 and 2, 90 min for study 3, and 180 min for studies 4 and 5).…”
Section: Methodsmentioning
confidence: 99%
“…Protein nitration has previously been reported in animal models to be a potential link between hypoglycemia and cell damage. These findings may therefore contribute to the development of novel targeted strategies for the prevention of brain lesions which may occur in severe neonatal hypoglycemia [61] .…”
Section: Potential Confounding Factors and Limitations Of The Studymentioning
confidence: 91%